Solid, double-metal cyanide catalysts for synthesis of hyperbranched polyesters and aliphatic polycarbonates - Sebastian, Joby; Darbha, Srinivas (Journal of Chemical Sciences, 2014)
Fe-Zn and Co-Zn double-metal cyanide (DMC) complexes exhibit highly efficient and selective catalytic activity for synthesis of hyperbranched polyesters (glycerol succinic acid (G-SA) and glycerol adipic acid (G-AA)) and aliphatic polycarbonates (via., alternative co-polymerization of cyclohexene oxide and CO2), respectively. The influence of method of preparation of DMC, in particular the mode of addition of reagents, on its physicochemical and catalytic properties was investigated. Co-Zn DMC was found highly selective for polycarbonate (than polyethers) formation. Catalysts prepared using tert-butanol and PEG-4000 as complexing and co-complexing agents, respectively, were found superior to those prepared without these agents. Apart from its role as a coordinating ligand, tert-butanol activated the Lewis acidic Zn2+ sites for reactions in polyester and polycarbonate formation. Hydrophobicity, micro-mesoporosity, acid strength and the amount of coordinated complexing agent are some of the crucial factors influenced the catalytic activity of DMC complexes.
Keywords: aliphatic polycarbonate; CO2 utilization; Double-metal cyanide complex; heterogeneous catalysis; hyperbranched polyester